'I've always done what I was told by the medical people': a qualitative study of the reasons why older adults attend multifactorial falls risk assessments mapped to the Theoretical Domains Framework. Issue 2 (18th February 2020) - Racine, Emmy; Soye, Anna; Barry, Patrick; Cronin, Finola; Hosford, Orla; Moriarty, Eileen; O'Connor, Kieran A; Turvey, Spencer; Timmons, Suzanne; Kearney, Patricia M; McHugh, Sheena M
Abstract : Objectives: Multifactorial falls risk assessments reduce the rate of falls in older people and are recommended by international guidelines. Despite their effectiveness, their potential impact is often constrained by barriers to implementation. Attendance is an issue. The aim of this study was to explore why older people attend community-based multifactorial falls risk assessment clinics, and to map these reasons to a theoretical framework. Design: This is a qualitative study. Semi-structured interviews were conducted and analysed thematically. Each theme and subtheme were then mapped onto the Theoretical Domains Framework (TDF) to identify the determinants of behaviour. Participants: Older adults (aged 60 and over) who attended community-based multifactorial falls risk assessments. Results: Sixteen interviews were conducted. Three main themes explained participants' reasons for attending the multifactorial risk assessment; being that 'type of person', being 'linked in' with health and community services and having 'strong social support' . Six other themes were identified, but these themes were not as prominent during interviews. These were knowing what to expect, being physically able, having confidence in and being positive towards health services, imagining the benefits given previous positive experiences, determination to maintain or regain independence, and being 'crippled' by the fear of falling . These themes mapped on to nine TDF domains: 'knowledge', 'skills', 'social role and identity', 'optimism', 'beliefs about consequences', 'goals', 'environmental context and resources', 'social influences' and 'emotion'. There were five TDF domains that were not relevant to the reasons for attending. Conclusions: These findings provide theoretically based factors that influence attendance which can be used to inform the development of interventions to improve attendance to falls prevention programmes.